"Come what may, we bring those resources to play": Narratives, future‐making, and the case of bauxite extraction at Atewa Forest, Ghana. Issue 2 (7th December 2021) - Purwins, Sebastian
Abstract: The Ghanaian government aims to develop an integrated bauxite–aluminium industry and seeks to further bauxite extraction at several sites across the country. This vision is embedded within the political agenda "Ghana Beyond Aid, " introduced by the country's president, Nana Akufo‐Addo. One possible mining area is Atewa Forest, one of the few remaining intact upland evergreen rainforests in Ghana. This study highlights the important narratives local NGOs use to mobilise against bauxite mining at Atewa Forest: (a) the case of environmental justice with a strong focus on clean water and (b) the foreign Chinese influence. Both narratives have gained national as well as international attention. However, the government avoids direct discussion and legitimises extraction through the newly created political agenda Ghana Beyond Aid. The latter is better understood as a future‐making practice, a practice creating a single development path that only needs to be managed. At the same time, revenue from refined bauxite finances huge infrastructure projects that are the foundation of this political agenda. In addition, this legitimation to extract bauxite appears to be powerful because it is linked to broader global narratives about modernisation and economic growth. Abstract : Bauxite mining at Atewa Forest is linked with future promises about development that make the extraction appear as something achievable and without alternatives. Looking at "Ghana Beyond Aid" as a future‐making practice gives more attention to how the resource bauxite gains importance and its extraction gains legitimisation.